Wakaf Uang dalam Perspektif Empat Mazhab dan Implementasinya di Indonesia - Rahmat, Rahmat; Nurjannah, Mauliya Redyan (Fakultas Syariah UIN Prof. K.H. Saifuddin Zuhri, 2024)
This research aims to understand the law of cash waqf from the perspective of the four madhhabs (Syafi'i, Hanafi, Maliki, and Hambali) and its implementation in Indonesia. The method used is literature research with a qualitative approach. The Shafi'i and Hambali schools tend to be strict in their views on cash waqf, with the majority of scholars stating that cash waqf is prohibited because the object of waqf must retain its physical form (ain) after use, such as dinars or dirhams. While there is a minority view from the more tolerant Shafi'i scholars, the Maliki school gives some leeway to cash waqf if it is based on the waqf of movable objects. On the other hand, the Hanafi and Maliki schools allow cash waqf based on istihsan bi al-'urf, as cash waqf has become an accepted custom in both schools. Based on these four madhhabs, it can be concluded that there are two views regarding the law of cash waqf. The Shafi;i and Hambali schools reject cash waqf because they argue that waqf must be in the form of objects that are fixed and not used up in order to maintain the permanence of waqf assets, while the Maliki and Hanafi schools allow cash waqf based on the view that waqf assets are not only seen from movable and immovable objects but are more complex than that that waqf assets such as cash waqf must focus on the aspects of the usefulness the waqf object.